Identifying behaviours for survival and wellness among people who use methamphetamine with opioids in British Columbia: a qualitative study - Jenny Corser; Heather Palis; Mathew Fleury; Jess Lamb; Kurt Lock; Jenny McDougall; Amiti Mehta; Cheri Newman; Heather Spence; Jane A. Buxton (BMC, 2022)
Abstract Background British Columbia (BC) has been in a state of public health emergency since 2016, due to the unprecedented numbers of fatal and non-fatal drug toxicity (i.e. overdose) events. Methamphetamine detection in illicit drug toxicity deaths increased from 14% in 2012 to 43% in 2020 suggesting a concerning trend of concurrent methamphetamine and opioid use in BC, consistent with rising patterns identified across North America. People who use methamphetamine concurrently with opioids face an elevated risk of harm. This study aimed to identify behaviours for survival and wellness practiced by people who concurrently use methamphetamine and opioids. Methods One-on-one semi-structured interviews were conducted by peer research assistants in person and by telephone. Thematic analysis was carried out to identify patterns in behaviours participants described as important to their safety in the context of concurrent use of methamphetamine and opioids. Results Participants (n = 22) were distributed across the province with at least four participants from each of the five geographic health regions: 64% self-identified as men, and 50% self-identified as Indigenous. Daily methamphetamine use was reported by 72.7% of participants, and 67.3% reported using alone either often or always. Participants made several considerations and adaptations in order to balance the perceived benefits and risks of their use of methamphetamine with opioids. Two overarching themes were identified to describe how participants adapted their use for survival and wellness. The first was personal safety behaviours which included self-regulation and self-care behaviours. The second was interpersonal safety behaviours which included using alongside peers, and engaging with peer-led services (e.g. community outreach organizations) and public health-led services (e.g. overdose prevention sites) to reduce the risk of harm. Participants identified many gaps in available services to meet their diverse needs. Conclusions This manuscript identified diversity in participants' methamphetamine and opioid use (i.e. frequency, route of administration), and a range of behaviours that were performed to improve wellness and survival while using methamphetamine and opioids. Harm reduction and treatment responses must be robust and adaptable to respond to the diversity of patterns of substance use among people who use methamphetamine and opioids concurrently, so as to not perpetuate harm and leave people behind.